A multicenter retrospective study assessing progression of biliary sludge in dogs using ultrasonography. (15th April 2022) - Butler, Thomas; Bexfield, Nick; Dor, Cecile; Fantaconi, Nicoletta; Heinsoo, Iris; Kelly, Darren; Kent, Andrew; Pack, Matthew; Spence, Susanna J.; Ward, Patricia M.; Watson, Penny; McCallum, Katie E.
Abstract: Background: Biliary sludge (BS) frequently is identified on ultrasonographic examination and is described as incidental. It is hypothesized that biliary stasis and hypersecretion play a role in both BS and gallbladder mucocele (GBM) formation. Recent studies have documented similarities in composition of BS and GBM, and there are several examples of progression from BS to GBM in the veterinary literature. Objectives: To assess the relationship between the presence of BS and later development of GBM in dogs, over time periods >12 months. Animals: A total of 154 dogs with BS and ultrasonographic follow‐up >12 months. Methods: Medical records were retrospectively collected from 9 UK‐based referral centers for all available time points. A semiobjective scoring system was used to track volume of BS within the gall bladder (GB) over time. Results: Twenty dogs developed GBM during the study period. Shetland Sheepdogs (odds ratio [OR], 40.99; 95% confidence interval [CI], 3.61‐465.95; P = .003) and Border Terriers (OR, 11.66; 95% CI, 3.28‐46.63; P < .001) were independent risk factors for the development of GBM. Non–gravity‐dependent BS (NDBS) was noted to form before GBM development in 9/20 dogs, and breeds at‐risk for GBM were more likely to have NDBS. Odds for the development of GBM increased with BS score. Conclusions and Clinical Importance: Dogs with NDBS may be at risk for the development of GBM and a stratified BS scoring system could allow for semiobjective monitoring over time, particularly in at‐risk breeds.